The improvement of technical skill at the stage of the specialized basic preparation in fitness by means of powerlifting - Ivan Ivanov (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to develop methodical recommendations of the improvement of technical skill at the stage of the specialized basic preparation in fitness by means of powerlifting. Material and Methods: masters of sports in powerlifting and candidates for the master of sports in powerlifting - members of a national team on weightlifting and powerlifting of the Kharkov area took part in the research. Methods were used: theoretical analysis and generalization, analysis of scientific literature, pedagogical supervision, pedagogical experiment, video registration method, methods of mathematical statistics. Results: we developed a number of methodical recommendations which are submitted on finishing technical skill on the basis of the analysis of technique of a performance of the competitive exercise deadlift which is made by means of the program Dartfish by highly skilled sportsmen. As a result of the experiment it is established that the gain of result was more significant in the experimental group which was engaged by the developed technique. Conclusions: it is experimentally proved that the use of computer programs of video registration allows improving qualitatively the feedback between a coach and a sportsman, optimizing the process of training of a sportsman and correction of his technique, increasing the gain of sports result